Granola consumption with multiple prebiotics in Japanese participants increases Bifidobacterium abundance and improves stress and subjective sleepiness - Sasaki, Hiroyuki; Masutomi, Hirofumi; Nakamura, Shuji; Tanigawa, Chiemi; Cui, Yufei; Ishihara, Katsuyuki; Yanagisawa, Masashi; Kokubo, Toshio (Frontiers in Nutrition, 2025)
BackgroundSleep is essential for physical and mental health. However, stress-related sleep disorders are common in Japan, and the gut–brain axis may play a role in sleep and stress management. This study investigated whether the consumption of granola containing multiple prebiotic ingredients could alleviate stress and improve insomnia in adults with stress-related sleep problems, regardless of individual differences in the gut microbiota. Additionally, we aimed to investigate the relationship between changes in gut microbiota and the observed improvements.MethodA single-arm uncontrolled trial was conducted with 27 adults with high stress levels and sleep disturbance. The participants consumed 50 g of prebiotics-containing granola daily for 8 weeks. Subjective sleep quality was assessed using the Athens Insomnia Scale, Epworth Sleep Scale, and Oguri-Shirakawa-Azumi Sleep Inventory-Middle-aged and Aged version (OSA-MA). Stress levels were assessed by administering the Brief Job Stress Questionnaire and Profile of Mood States 2nd edition (POMS2). Gut microbiota composition was analyzed using 16S rDNA sequencing.ResultsAfter 8 weeks, subjective insomnia scores and sleep onset and maintenance improved significantly, whereas the stress and mood disturbance scores decreased significantly. Gut microbiota analysis showed that the relative abundance of Bifidobacterium increased, whereas that of Bacteroides decreased. Correlation analysis suggested a significant association between increased Bifidobacterium level and reduced stress (r = −0.39, p = 0.0035) and insomnia levels (r = −0.3, p = 0.026).ConclusionPrebiotics-containing granola improved subjective sleep quality and reduced stress in adults with stress-related sleep disturbances, which may be attributed to alterations in gut microbiota, particularly the increase in Bifidobacterium abundance.